Didattica e inclusione scolastica - Inklusion im Bildungsbereich Emergenze educative Neue Horizonte - Auer, Petra (bu,press, 2022)
The inequalities in education, which have also been exposed by the pandemic, highlight the need for alternatives and new horizons. The seventh edition of the conference series "Didattica e Inclusione Scolastica - Inclusion in Education", which was organized for the first time under the direction of the Competence Center for Inclusion in Education of the Free University of Bozen-Bolzano, offered a space to deal with the priorities of a just and inclusive education during this time. This volume opens up a dialogue on inclusive didactics, which builds a bridge between german- and Italian-speaking traditions through its multilingual and intercultural orientation. The twelve contributions open up from different perspectives theoretical references, methods and instruments for the development of an inclusive school with a special focus on didactics.